THE EFFECT OF FLUCTUATION WORLD OIL PRICES AND THE RUPIAH EXCHANGE RATE ON ECONOMIC GROWTH IN INDONESIA - Ulfa Ajnura; Hijri Juliansyah (LPPM Universitas Malikussaleh, 2021)
This study examined the effect of fluctuations in world oil prices and the rupiah exchange rate on economic growth in Indonesia in the short and long term. This study used time-series data for 31 years. The analytical model used was the Autoregressive Distributed Lag model. The results show in the short term showed that world oil prices had a positive but insignificant effect on economic growth in Indonesia, while the rupiah exchange rate had a negative and significant effect on economic growth in Indonesia. In the long term, world oil prices had a positive and significant effect on economic growth in Indonesia. The rupiah exchange rate has a negative and significant effect on economic growth in Indonesia. It indicated that in the short term, the rupiah exchange rate had an influence or contribution to economic growth in Indonesia, and in the long term, world oil prices had an effect or contribution to economic growth in Indonesia.